The Effect of Trust on Organizational Citizenship Behavior (OCB) on Officers at Class IIB Kudus State Detention Center - Halilintar, Ilham Saputra; Kusmiyanti, Kusmiyanti (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
OCB is the behavior of organizational members who provide voluntary assistance outside the job description which is very beneficial for the organization because it can increase effectiveness and efficiency in the organization. Many factors can affect OCB, one of which is trust. This study aims to examine the effect of trust on Organizational Citizenship Behaviour (OCB) on officers at Class IIB Kudus State Detention Center. This study uses quantitative methods with research subjects all officers at Class IIB Kudus State Detention Center. The purpose of this study was to determine how much influence trust has on Organization Citizenship Behavior on officers. The sample in this study amounted to 46 officers obtained with the saturated sample technique. The data in this study were obtained through distributing questionnaires and using data analysis with the simple linear regression analysis method and processed in the SPSS program. The research procedures tested include validity testing, reliability testing, normality testing and research hypothesis testing. The results of the simultaneous test (f) and partial test (t) found that the value of f arithmetic was greater than f table (10.401> 4.06) and t arithmetic was greater than t table (3.225 > 2.015). This shows that there is an influence of the Trust variable on the Organizational Citizenship Behavior (OCB) variable and there is a positive and significant relationship between the two variables. This means that trust has a positive influence on OCB on officers at Class IIB Kudus State Detention Center.